The effect of fancy rope jumping exercise on creativity of elementary school students - Chao Wang; Xiaoxiao Zhang; Hansen Li; Guodong Zhang (Quality in Sport, 2022)
Purpose: To explore the effects of 6 months of moderate intensity fancy rope jumping exercise on the creativity of elementary school students.